Perception of the Impact of Bullying to the Selected High School Students’ Academic Performance - Domalaon, Jev C.; Dunghit, Jean C.; Magos, Darlene Joy; Vedana, Esther; Echanis, Sherill; Siquig, Lilibeth (International Journal of Psychosocial Rehabilitation, 2020)
Education is essential for everyone. It is an indispensable part of life both personally and socially, undeniable for every single person. To get the most out of a good education, children need to go to school every day. Unfortunately, there are some hindrances to the attainment of education, and one of which is the problem of bullying. Nowadays, the issue of bullying has greatly affect the security of various institutions. The dilemma has not only affects the education of children, but, bullying leaves them scars not only physically but psychologically as well. This study aimed to determine the relationship between bullying and academic performance that may help solve problems on the bullying of students in schools. It made use of the descriptive-survey method of research to accomplish the task of identifying the forms, causes, and effects of bullying in schools. Simple random sampling was used in selecting the respondents-students, teachers, and parents as well. The records in the Guidance Office were utilized to acquire the needed information regarding the profile of the students who had bullying cases in the school. A total of 240 served as respondents, 80 students, 80 parents, and 80 teachers. The respondents were from different public and private high schools in the City of San Jose del Monte, Bulacan. The majority of the respondents considered "Problems at home" as the most common reason why students bully others. In terms of academic performance was a significant relationship between the student respondents’ academic grade when grouped according to gender and birth order.